2020
DOI: 10.1080/13607863.2020.1805723
|View full text |Cite
|
Sign up to set email alerts
|

Are older adults also at higher psychological risk from COVID-19?

Abstract: Objective: Given the lack of information on the psychological impact of COVID-19 on people aged !60, we aimed to describe their psychological responses to this pandemic and lockdown situation and compare them with those under 60 years of age. Methods: Secondary analysis of a larger online cross-sectional study designed to determine the psychological impact of the COVID-19 pandemic and lockdown across Spain. We analyzed a total of 1690 respondents aged !60 years and compared them with 13,363 respondents under 6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

13
91
2
6

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(120 citation statements)
references
References 24 publications
13
91
2
6
Order By: Relevance
“…Recent evidence from Spain showed how older adults were less likely to suffer from psychological distress as a result of the pandemic than people aged below 60. 18 Nevertheless, overall the pandemic is having a heightened impact on the mental health of the general population. 19 20 Engaging in social activities can be one avenue to help maintain good mental health.…”
Section: Discussionmentioning
confidence: 99%
“…Recent evidence from Spain showed how older adults were less likely to suffer from psychological distress as a result of the pandemic than people aged below 60. 18 Nevertheless, overall the pandemic is having a heightened impact on the mental health of the general population. 19 20 Engaging in social activities can be one avenue to help maintain good mental health.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies showed that social isolation has a detrimental effect on the physical and mental health of older people 1, 2 . A recent study conducted after a wave of the COVID‐19 pandemic detected depressive symptoms and anxiety symptoms in approximately 21% and 2% of individuals, respectively, and found that these symptoms occurred less in older individuals than in younger individuals 3 . In Turkey, a curfew has been declared for people age ≥65 and those with chronic diseases.…”
Section: Introductionmentioning
confidence: 99%
“…The fact that religion orients people to the dimensions of self-e cacy provides a way of approaching the disease and the strategy to achieve positive mental health. [22][23]26 In distinguishing the sacred and the profane, Emile Durkheim's writing of The Elementary Forms of Religious Life (1912) noted that the distinction between the sacred and the profane is not subject to the evil/good dichotomy. 40 Thus, COVID-19 and the attendant effects are interpreted as retributive justice (because it threatens the human race) or the effect of an opposing force (evil), which is in contention with the Supreme Being.…”
Section: Discussionmentioning
confidence: 99%
“…40 Thus, COVID-19 and the attendant effects are interpreted as retributive justice (because it threatens the human race) or the effect of an opposing force (evil), which is in contention with the Supreme Being. 23 In this case, adherents seek forgiveness and protection from the Supreme Being. Seeking forgiveness and protection and believing that one has obtained it has bene ts for positive mental health.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation